Implementasi Manajemen Pendidikan Teknologi dan Vokasi dalam Menghadapi Kurikulum Merdeka Belajar - Saniyatul Hikmah; Alfredo Arianto Permana Putra; Marniati; Dewanto (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2023)
The independent learning curriculum is a new curriculum that is being promoted by the Minister of Education and Culture at this time. Many teachers are still adjusting this new curriculum. This study aims to elaborate on the implementation of technology and vocational education management in Vocational High Schools (SMK) Surabaya in the face of an independent learning curriculum. Using this type of qualitative research so that the data produced is descriptive. Data sources obtained from principals and representatives of various fields (student affairs, curriculum, facilities and infrastructure) as well as teachers along with supporting documents. Collecting data using interview, documentation and observation techniques. Data analysis is carried out after collecting all the supporting data, then the data is reduced, played data to conclusions. This research was conducted at one of the SMK Surabaya odd semester TP. 2022/2023. From this research, it can be produced that the curriculum used by SMK Surabaya is an independent learning curriculum. In the implementation of education management, this curriculum has not found weaknesses or advantages because it has only been running for a few months. So the author gives advice to use and pay attention to swot analysis in order to get better data.